Pendokumentasian Edukasi Pasien oleh Tenaga Keperawatan di Instalasi Rawat Jalan RSUD Kota Dumai - Roziah Roziah; M Kamali Zaman; Herman M Purwonegoro (Universitas Batanghari Jambi, 2022)
Hospital management needs to solve the problems that exist in the hospital by using the scientific method. The purpose of this study is to perform problem identification process, process of selecting problem priorities and problem solving recommendations, namely the problem of documenting patient education by nursing staff at Instalasi Rawat Jalan of RSUD Kota Dumai. The research method used is a qualitative research method. The sampling method is purposive sampling. The number of informants is 10 people. The results of the study were from the man factor, lack of motivation, lack of compliance, lack of capacity of nursing staff as educators and mental models. From the method factors, lack of time from the nursing staff, lack of staffing functions from the Head Room of Instalasi Rawat Jalan, there is no routine supervision schedule from the Head Room of Instalasi Rawat Jalan and manual recording system for BPJS claims. From material factors, leaflets were underutilized and there was no educational format for re-control patients. The conclusions there is a need to improve the management function of the Head Room of Instalasi Rawat Jalan, training to increase the capacity of nursing staff as educators at Instalasi Rawat Jalan, optimizing the role of administrative staff to fill out BPJS claim files, increase SIMRS and evaluate the use of leaflets by the PKRS Installation at RSUD Kota Dumai.